Implementasi Kurikulum Cambridge di Sekolah Menengah Pertama - Rachel Anastasya Christiana; Achmad Supriyanto; Juharyanto Juharyanto; Rachel Anastasya Christiana; Achmad Supriyanto (Universitas Negeri Malang, 2022)
Abstract: This research aims to describe a number of things, which cover the basic concepts of implementing the Cambridge curriculum, the Cambridge curriculum implementation process, and the results obtained by the school through implementing the Cambridge curriculum. The research method used in this study is a qualitative research type of case study. The results of this study are: (1) The concept of the Cambridge curriculum in Junior High School is the use of this curriculum aimed at creating a generation that has the principle of confidence; (2) The implementation of the Cambridge curriculum in Junior High School is divided into three stages of process, namely the process of introduction / socialization, the process of implementation, and the evaluation process; (3) The results of the Cambridge curriculum implementation in Junior High School are students can continue to the next level using the Cambridge A Level curriculum, many Junior High School’s student have many achievements in the academic field, and becomes one of the best Cambridge schools in Indonesia. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan beberapa hal, yang meliputi konsep dasar penerapan kurikulum Cambridge, proses implementasi kurikulum Cambridge, serta hasil yang didapat sekolah melalui pengimplementasian kurikulum Cambridge. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif jenis studi kasus. Hasil dari penelitian ini adalah: (1) Konsep kurikulum Cambridge di Sekolah Menengah Pertama adalah penggunaan kurikulum ini bertujuan untuk menciptakan generasi yang memiliki prinsip percaya diri; (2) Implementasi kurikulum Cambridge di Sekolah Menengah Pertama dibagi menjadi tiga tahapan proses, yaitu proses pengenalan/sosialisasi, proses penerapan, dan proses evaluasi; (3) Hasil implementasi kurikulum Cambridge di Sekolah Menengah Pertama adalah peserta didik dapat melanjutkan ke kurikulum Cambridge A Level, peserta didik di Sekolah Menengah Pertama banyak yang berprestasi di bidang akademik, dan Sekolah Menengah Pertama menjadi salah satu sekolah Cambridge terbaik di Indonesia.